Bank Credit and Loan Repayment During Covid-19 In Kabale District: A Case of Lyamujungu SACCO. - Byamukama, Dicky (Kabale University, 2023)
This study was conducted with the aim of investigating the impact of bank credit on loan repayment during COVID-19 at Lyamujungu SACCO. Three specific objectives guided this study that included: to establish the effect of borrower character on loan repayment during COVID -19 pandemic; to examine the effect of borrower’s capacity to pay on loan repayment during COVID -19 pandemic; and, to establish the effect of borrower’s credit period on loan repayment during COVID-19 pandemic at Lyamujungu SACCO. A cross-sectional survey design was used to examine, characterize, and compare bank credit and loan repayment in Kabale District using Lyamujungu SACCO as a case study. This was approached using qualitative and quantitative methods. With the help of a questionnaire and interviews, data was collected from 108 clients of Lyamujungu SACCO. In addition, interviews were conducted with the general manager, branch managers and loans officers. The collected data was cross-checked for errors of omission and completeness, coded and analysed using SPSS computer package. Data was presented in form of tables as frequencies, percentages, standard deviation, mean. Significance levels were determined for hypothesis. Results for the first study objective revealed that the outbreak of Covid-19 led to a drop in labour productivity growth (4.73, SD =.523), a major issue that affected borrowers’ character in loan repayment. The second study objective revealed that SACCOs started giving less loans in comparison to what borrowers applied for (M=4.05, SD=1.256) and closed very early during Covid-19 pandemic (M=3.73, SD=1.378) all of which affected the borrower’s capacity to repay loans. Finally, results on the third objective indicated that quarantine and social distancing which blocked financial opportunities (M=4.78, SD=.418), consequences that drove SACCO members into loan repayment failure (M=4.70, SD=.459) and loss of savings leading to absolute poverty (M=4.56, SD=.600) were the major factors that determined the borrower’s credit on loan repayment during Covid-19 pandemic. Results from null hypothesis testing on the three items was rejected indicating borrower’s character (.000), borrower’s capacity (.040) and borrower’s credit period (.001). Thus the study concluded that there is evidence to suggest that the distribution of the mean score of each of the three variables is not the same across the ability of the borrower to repay the borrowed loan. The study recommends SACCOs to seriously consider having in place effective credit standards, credit policy, credit terms and collection policies or procedures as mechanisms to guide their business, since the effectiveness of credit management is important to the successful management of banking institutions.